EULAR points to consider in the development of classification and diagnostic criteria in systemic vasculitis. Issue 10 (6th May 2010) - Basu, Neil; Watts, Richard; Bajema, Ingeborg; Baslund, Bo; Bley, Thorsten; Boers, Maarten; Brogan, Paul; Calabrese, Len; Cid, Maria C; Cohen-Tervaert, Jan Willem; Flores-Suarez, Luis Felipe; Fujimoto, Shouichi; et al.
Abstract : Objectives: The systemic vasculitides are multiorgan diseases where early diagnosis and treatment can significantly improve outcomes. Robust nomenclature reduces diagnostic delay. However, key aspects of current nomenclature are widely perceived to be out of date, these include disease definitions, classification and diagnostic criteria. Therefore, the aim of the present work was to identify deficiencies and provide contemporary points to consider for the development of future definitions and criteria in systemic vasculitis. Methods: The expert panel identified areas of concern within existing definitions/criteria. Consequently, a systematic literature review was undertaken looking to address these deficiencies and produce 'points to consider' in accordance with standardised European League Against Rheumatism (EULAR) operating procedures. In the absence of evidence, expert consensus was used. Results: There was unanimous consensus for re-evaluating existing definitions and developing new criteria. A total of 17 points to consider were proposed, covering 6 main areas: biopsy, laboratory testing, diagnostic radiology, nosology, definitions and research agenda. Suggestions to improve and expand current definitions were described including the incorporation of anti-neutrophil cytoplasm antibody and aetiological factors, where known. The importance of biopsy in diagnosis and exclusion of mimics was highlighted, while equally emphasising its problems. Thus, the role of alternative diagnostic tools such as MRI, ultrasound and surrogate markers were also discussed. Finally, structures to develop future criteria were considered. Conclusions: Limitations in current classification criteria and definitions for vasculitis have been identified and suggestions provided for improvement. Additionally it is proposed that, in combination with the updated evidence, these should form the basis of future attempts to develop and validate revised criteria and definitions of vasculitis.